Reflections on facilitating a trauma-informed clinical supervision group with housing first staff. Issue 1 (2nd April 2020) - Radis, Brie
ABSTRACT: Housing First is a recovery-oriented approach that moves individuals from homelessness to permanent supported housing. The premise of housing first is that housing is a basic right and individuals facing houselessness become better prepared to address the challenges they will face once they are housed and offered support. My story explores the experiences that come up in a supervision group for housing first staff members who are addressing social justice issues on a daily basis. But where is the justice for this overworked and underpaid group? In the course of my story, I weave in my personal experience as a housing first advocate, which led me to advocate for the supervision group and, eventually, to increase the time and frequency of what became a sacred space for learning, support and self-care.